Influencing Factors for Corporate Performance of Carbon Credit Trading Business Management in Eastern Economic Corridor (EEC) Area Thailand - Iamsaard, Sarawoot; Khantanapha, Napaporn (Ph.D. in Social Sciences Journal, 2026)
This research article aimed to achieve three main objectives: (1) To examine the levels of green management factors, business strategies, carbon credit trading, motivation and cooperation, and organizational performance within the Eastern Economic Corridor (EEC) of Thailand;(2) To analyze the causal relationships in the proposed structural equation model, in which the antecedent factors included green management, business strategy, and carbon credit trading, while the consequence factors were motivation, cooperation, and organizational performance; and(3) To propose a sustainable strategic operational model for carbon credit trading businesses in the EEC region of Thailand.A mixed-method approach was adopted. Quantitative data were collected from 300 participants, including executives, managers, and production supervisors of Category Ror.Ngor.4 industrial factories located in Chachoengsao, Chonburi, and Rayong—the core EEC provinces. Data were analyzed using Structural Equation Modeling (SEM) to validate causal relationships, complemented by qualitative in-depth interviews with experts to capture strategic and policy perspectives in the business sector. The results revealed that green management, business strategies, and carbon credit trading had both direct and indirect significant effects on organizational performance. Motivation and cooperation acted as mediating variables that enhanced adaptability and competitiveness within the emerging green economy.Organizations that successfully integrated environmental management into their business strategies and collaborations demonstrated higher cost efficiency, innovation capacity, and sustainable performance in the long term.